Shared Care Planning: how to implement it in oncology (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper aims to define how to implement shared care planning (SCP), in oncology. Starting from the pathway and needs of the cancer patient, stakeholders and decision-making processes involved in SCP are identified. The IOV experience is also presented as an example of the simultaneous care model as the ideal time to SCP with the patient and family. Although the oncology field is one of the areas in which SCP is ideally placed, as a safeguard for the patient and health care providers, to date many organizational, training, and cultural problems do not allow for systematic dissemination of SCP in the oncology field.
Keywords: Advance care planning; shared care planning; cancer patients; patient journey; simultaneous care